Smart parking system / Muhammad Fahmi Ahmad Shafee & Muhammd Afiq Omar - Ahmad Shafee, Muhammad Fahmi; Omar, Muhammd Afi (2015)
With the development of automobile industry, the number of cars on the road is greatly increasing. Otherwise, the number of beginner drivers is increasing as well. For the rookie drivers, how to reverse is always a troublesome operation. In this project, smart system of ultrasonic car parking with different display mode has been designed. A buzzer or a beeper which is a signal device is used to show the distance of the car with the obstacles behind it. HC-SR04 is used as sensor detecting obstruction behind the car when reverse. Therefore, Smart Parking System technology could be used in our daily life application. It is to avoid car collision and measure distance. This device is the end of best technology device that can be use in detecting obstruction behind the car when reverse. There is a distance limitation in ultrasonic sensor to measure a distance. The result the project showed that the system's efficiency is not a hundred percent successfully because of error of the sensor sensitivity itself.